And thus the Circle has got its seventh publication - Faltýnek, Dan (Bohemica Olomucensia, 2013)
By simple argumentation I show that it is not possible to build explanation of the history of linguistics on nonlinguistic (nontheoretical/nonconceptual) facts. External coefficients are very important in the development of linguistic science, but in the explanation of linguistic history they must be only ilustrative. This broad issue is presented by contention about linguistic purism, whose two protagonists are Prague Linguistics Circle and Jiří Haller.